Convergencia de la NAIRU: el caso colombiano (2012)
This paper analyzes the NAIRU from the perspective of the Extended Phillips Curve. It takes an overview of the work done in the field, and, makes several estimates of the NAIRU. The intention of the paper is to apply these estimates to the Colombian economy during the period 1984-2011 taking into account variables such as the consumer price index (CPI), the unemployment rate and the rate of wages in the industry. The results suggest that there is no consensus on the value of the NAIRU, as this depends on the methodology applied in the calculation, and therefore questions its use in monetary policy.